2020
DOI: 10.1155/2020/6094712
|View full text |Cite
|
Sign up to set email alerts
|

Expectation and Satisfaction with Nursing Care among Hypertensives Receiving Care at a Resource-Constrained Hospital in Ghana

Abstract: Background. Hypertension accounts for a third of the global preventable premature deaths. In Sub-Saharan Africa, hypertension is the most rapidly increasing cardiovascular disease (CVD) and the second leading cause of death. Proper management of hypertension requires adherence to management by patients and this is partly possible if patients feel satisfied with the nursing care they receive. Satisfaction with nursing care is only possible if there is a congruence between the expectations of care and the actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…A 2020 in-depth interview by Konlan et al stated that when patients were enquired about their expectations for care prior to admission, patients reported that they expected nurses to be very responsive to their needs and should proactively meet those needs, to treat pain as an emergency, and comfort them when they are in pain. 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2020 in-depth interview by Konlan et al stated that when patients were enquired about their expectations for care prior to admission, patients reported that they expected nurses to be very responsive to their needs and should proactively meet those needs, to treat pain as an emergency, and comfort them when they are in pain. 27 …”
Section: Resultsmentioning
confidence: 99%
“…A 2020 in-depth interview by Konlan et al stated that when patients were enquired about their expectations for care prior to admission, patients reported that they expected nurses to be very responsive to their needs and should proactively meet those needs, to treat pain as an emergency, and comfort them when they are in pain. 27 A study by Gebrezgi et al found that a patient's economic status can affect the management of hypertension in different ways. Eritrea provides antihypertensive medications free of charge, and economic status does not appear to https://doi.org/10.2147/PPA.S388356…”
Section: The Preferences and Expectations For Management And Treatmentmentioning
confidence: 99%
“…Public hospitals in Accra have higher numbers of patients as compared to the private facilities [18,20,21]. This study therefore involved only health workers in the public health facilities who were at increased risk of burnout due to their high patient numbers [22,23]. The situation is exacerbated by the emergence of COVID-19 pandemic, whereby Accra reportedly has the highest number of COVID-19 cases [6] and thus predisposing health workers in public hospitals in the city to increased workload and job-related burnout [2,4,6].…”
Section: Settingmentioning
confidence: 99%
“…Thus, these socio-cultural orientations are interconnected with religiosity in Africa that negatively influence healthcare access and adherence. The situation is made worse with high poverty and dependency in Africa ( Tang and Qin, 2015 ), so the real decision for not approving hospital care could be more than religiosity especially when hospital treatment is deemed expensive ( Ugwu and De Kok, 2015 ) and the attitude of some healthcare professionals is also negative toward the poor patient ( Konlan et al, 2020 ). It is therefore likely that the lack of use of biomedical treatment could lead to the worsening of a disease and that contributes to suicidal ideations.…”
Section: Spirituality and Its Influence Of Healthcare Access And Carementioning
confidence: 99%
“…Nurses and midwives are mandated to respect the rights of patients and their families (Adinkrah, 2014) and to maintain confidentiality (Konlan et al, 2020). The patients are therefore not forced to take any treatment prescribed (Adinkrah, 2014).…”
Section: Introductionmentioning
confidence: 99%